IMPLEMENTASI SISTEM PEMBELAJARAN PEMISAH KELAS ANTARA SISWASISWI DALAM MENINGKATKAN PRODUKTIVITAS BELAJAR PADA MATA PELAJARAN PAI DI KELAS IX SMP ISLAM AL-MAARIF 01 SINGOSARI - Rahmawati Rahmawati; Azhar Haq; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This study aims to determine student learning productivity in the class separator learning system between male and female students at SMP Islam Al-Maarif 01 Singosari. The problem in this research is what are the factors that hinder the class separation learning system and how the implementation of the learning stsyem in SMP islam Al-Maarif 01 Singosari. The researcher uses a phenomology based qualitative approach by using acase study tipe of research. The resilts of this study have two positive and negative sides in the implementation of the class separator learning system, the positive side as long as the sytem is implementes, student behavior is better, delinquency that often occurs has decreased, and the negative side of male student tends to decrease and is not enthusiastic. Inte learning process.